2016
DOI: 10.1021/acs.jpca.6b02250
|View full text |Cite
|
Sign up to set email alerts
|

General AMBER Force Field Parameters for Diphenyl Diselenides and Diphenyl Ditellurides

Abstract: The General AMBER Force Field (GAFF) has been extended to describe a series of selenium and tellurium diphenyl dichalcogenides. These compounds, besides being eco-friendly catalysts for numerous oxidations in organic chemistry, display peroxidase activity, i.e., can reduce hydrogen peroxide and harmful organic hydroperoxides to water/alcohols and as such are very promising antioxidant drugs. The novel GAFF parameters are tested in MD simulations in different solvents and the (77)Se NMR chemical shift of diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 77 publications
6
32
0
Order By: Relevance
“…It is observed that the stable equilibrium structures differ mainly in spatial orientation of two phenyl rings in case of (PhSe) 2 and similar to (PhS) 2 system discussed earlier. Such observations are also reported in the literature for diphenylchalcogen systems including (PhTe) 2 based on conformation analysis . It is interesting to mention that for (PhSe) 2 system, it is possible to calculate chemical shift in the NMR spectra accurately from only these two equilibrium structures .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…It is observed that the stable equilibrium structures differ mainly in spatial orientation of two phenyl rings in case of (PhSe) 2 and similar to (PhS) 2 system discussed earlier. Such observations are also reported in the literature for diphenylchalcogen systems including (PhTe) 2 based on conformation analysis . It is interesting to mention that for (PhSe) 2 system, it is possible to calculate chemical shift in the NMR spectra accurately from only these two equilibrium structures .…”
Section: Resultssupporting
confidence: 76%
“…Such observations are also reported in the literature for diphenylchalcogen systems including (PhTe) 2 based on conformation analysis . It is interesting to mention that for (PhSe) 2 system, it is possible to calculate chemical shift in the NMR spectra accurately from only these two equilibrium structures . This certainly demonstrates that such methods have predictive ability and can be very useful to interpret experimental results and to provide better insights.…”
Section: Resultssupporting
confidence: 73%
“…On the other hand, for the Sec‐ and Tec‐based enzymes, no suitable parameters were available. Thus, we chose to derive the missing parameters for these residues by using a protocol and tools recently employed by some of us to derive GAFF (General AMBER Force Field) parameters for a series of organochalcogen compounds …”
Section: Methodsmentioning
confidence: 99%
“…For Lennard–Jones σ and ϵ parameters, we used 2.1200 Å and 0.2910 kcal mol −1 for Se and 2.2600 Å and 0.3980 kcal mol −1 for tellurium, consistent with previous work . During the simulation, they were combined according to the Lorentz–Berthelot mixing rules.…”
Section: Methodsmentioning
confidence: 99%
“…For a more extensive discussion on this conformational flexibility and its significant effect on the 77 Se chemical shift, the curious reader is referred to a recently published paper by some of us, [45] as well as others.…”
Section: Oxidation Of Phsesephmentioning
confidence: 99%